Mechanism of rotatory eye movements in opsoclonus. Issue 12 (December 1980) - Gresty, M A; Findley, L J; Wade, P
Abstract : 'Rotatory nystagmus', in which the visual axis of the eye moves involuntarily in the horizontal and vertical planes describing a closed loop trajectory, was analysed by means of combined video and electro-oculography in a patient with multiple sclerosis having numerous ocular signs of cerebellar disease. The rotations were sporadic, isolated single cycles having stereotyped, crescentiform loop shapes. Each consisted of a combination of a single cycle of vertical ocular flutter, the onset of which was followed 40 to 50 milliseconds later by a single cycle of horizontal ocular flutter. The timing relationship between flutters suggest that the vertical and horizontal systems had become somehow entrained. Rotatory nystagmus is saccadic in nature and arises from a unique timing relationship between vertical and horizontal flutter.